Infection control practices of dental clinicians at the University of the Philippines College of Dentistry (School Year 2012-2013) - Alberto, Kristel Anne P.
Introduction. Most dental practitioners fail to appreciate the infection potential presented by blood and saliva during treatment leading to diseases-most of which are preventable through proper infection control practices. This study aimed to determine, validate and verify the infection control practices of dental clinicians at the University of the Philippines College of Dentistry S.Y. 2012-2013.